Dynamically consistent intergenerational welfare - Lasse Mononen (Bielefeld University, Center for Mathematical Economics (IMW), 2024)
Dynamic consistency is crucial for credible evaluation of intergenerational choice plans that inherently lack commitment. We offer a general characterization for dynamically consistent intergenerational welfare aggregation. The aggregation is characterized by envy-guilt asymmetry in discounting with respect to future generations' utility: Higher utility than future generations' utility is discounted differently than lower utility than future generations' utility. This offers a simple and tractable characterization for the dynamically consistent choice rules.
urn:nbn:de:0070-pub-29872843
Keywords: 330; Dynamic consistency; discounting; social discount factor; preference aggregation